Musculoskeletal Outcome in Hemophilia: Bleeds, Joint Structure and Function, Activity, and Health-Related Fitness - Poonnoose, Pradeep M.; van der Net, Janjaap (Seminars in Thrombosis and Hemostasis, 2015)
Treatment in hemophilia is designed to reduce bleed frequency, minimize joint damage, and maximize functional independence and quality of life. Therefore, success of a factor replacement protocol is usually gauged by its ability to produce near “normal joints”—without any significant pathology. The most commonly used outcome measurement tools are based on the radiological and clinical assessment of joint arthropathy. To improve the sensitivity to early changes, the clinical scores have been refined, and imaging based on magnetic resonance imaging and ultrasonography has been initiated. Although these scores are useful in assessing the structure and function of a joint, they do not consider the impact of arthropathy on overall musculoskeletal function. They are also not capable of assessing the efficacy of interventions on functional independence, participation in life activities, and quality of life. The development of functional scores such as the Functional Independence Score for Hemophilia, the pediatric Hemophilia Activities List, and some quality of life measurement tools have helped provide a more comprehensive assessment of health. This article describes the psychometric properties and limitations of the various clinimetric tools that are used to assess musculoskeletal outcome in hemophilia and suggests an algorithm for their use in clinical practice.
Keywords: hemophilia; musculoskeletal outcome; activities; scores; assessment